2019
DOI: 10.1144/jgs2019-117
|View full text |Cite
|
Sign up to set email alerts
|

Regurgitalites – a window into the trophic ecology of fossil cephalopods

Abstract: Fossil oral ejecta that exclusively contain bivalved calcitic lower jaws of ammonites (=aptychi) from Late Jurassic Solnhofen-type deposits of southern Germany are described. Based on the symphysis length of aptychi the ammonite shell diameters were reconstructed, ranging from 5 to 170 mm. To identify the potential ammonite predator published reports on stomach contents, coprolites and ammonite-palaeopathology were critically assessed. Implementation of the actualistic approach, together with some functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 157 publications
1
25
0
1
Order By: Relevance
“…Cephalopods and arthropods noted from Polzberg section appear to be too small to produce these bromalites. Furthermore, these invertebrates have a rather alkaline gastric pH, and thus they produce regurgitates commonly containing specific hardparts (e.g., aptychi of ammonites) without etching-related features 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cephalopods and arthropods noted from Polzberg section appear to be too small to produce these bromalites. Furthermore, these invertebrates have a rather alkaline gastric pH, and thus they produce regurgitates commonly containing specific hardparts (e.g., aptychi of ammonites) without etching-related features 43 .…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that Palaeozoic and Mesozoic shelled cephalopods have been preyed upon by sharks and actinopterygian fishes 41,[43][44][45] . Noteworthy, Recent sharks and actinopterygian fishes are known to attack on Nautilus 46 .…”
Section: Discussionmentioning
confidence: 99%
“…A large number of taxa from the Solnhofen Archipelago, including 'fishes' and marine reptiles, supposedly fed on aquatic organisms such as cephalopods 4,9,[49][50][51][52] . The conical, slender and recurved shape of the tooth excludes several groups of fish and reptiles as possible culprits.…”
Section: Discussionmentioning
confidence: 99%
“…Additional indirect support for our hypothesis comes from a paper, published while this paper was initially under review, analyzing fossilized regurgitalites (orally ejected stomach contents) containing aptychi (calcitic lower jaws of ammonites) from 1 https://youtu.be/0tFz2ppx_DY; https://youtu.be/c02EZcjWNSE late Jurassic Solnhofen deposits (Hoffmann et al, 2019). From a detailed study of the regurgitalites, data on fossilized cephalopod digestive tract contents and other fossils found in the same or related deposits, the authors built a case (using some of the same literature reported here) that coleoid cephalopods and most likely vampyropods were the predators responsible for the origin of the regurgitated ammonite remains.…”
Section: Behavioral Observations Supporting the Presence Of Vomiting mentioning
confidence: 96%